Monetary policy frameworks in the Middle East and North Africa: How do they compare with other groupings?. (18th December 2020) - Cobham, David
Abstract: This paper presents a classification of the monetary policy frameworks (MPFs) of 19 MENA countries from 1974 to 2017. It identifies the key trends in the region and contrasts them with the trends among three other groups: advanced countries, emerging countries and Latin American countries. It considers likely reasons for the MPF choices of MENA governments and notes the economic performance associated in the region and elsewhere with different MPFs. It examines how these MPF choices relate to trends in central bank independence and transparency, and in democracy and governance. Finally, it brings these elements together in an argument that a move to democracy in the MENA countries could open the way to monetary policy frameworks that would offer improved economic performance.